Extracranial Internal Carotid Artery Aneurysms: case report of asaccular wide-necked aneurysm and review of the literature - Biasi, L.; Azzarone, M.; De Troia, A.; Salcuni, et al., P. (Acta Biomedica Atenei Parmensis, 2008)
Purpose: to describe a case of atherosclerotic Extracranial internal Carotid Artery Aneurysm (ECAA) with an unique “diverticulum-like” morphological structure, surgically treated and to review the experiences of major referral centers. Case Report: a 76-year-old woman presented with persistent dysphagia and transient hypophonia caused by a growing pulsatiling mass of the neck; duplex ultrasonography and angio-CT scan demonstrated a wide-necked, saccular aneurysm at the origin of the right Internal Carotid Artery (ICA). A total aneurysmectomy with patch angioplasty of the aneurysm of the neck on the carotid wall was successfully performed. No perioperative complications were encountered; at one year follow-up the patient was asymptomatic without any neurological complication and with carotid patency. Conclusions: open surgery remains the gold standard for the treatment of extracranial internal carotid artery aneurysms in terms of patency and reduced risk of adverse complications; endovascular procedures may, in selected cases, provide a valuable additional tool in the armoury of the physician.